A look at current oral and maxillofacial surgery (OMS) training requirements in comparison to 1994. Issue 3 (May 2015) - Rane, Talal; Taha, Samir; Nasser, Firas
Abstract Introduction The aim of the study was to give a clear view of the oral and maxillofacial surgery training requirements worldwide. Methods A survey was sent to the universities or associations that run or overlook running OMS programmes by e-mail or information was gathered directly through their website to collect information about each country's programme, whether it is dental-based training, medical-based, or dual degree-based, and scope of service. Result We recognized five types of OMS programmes worldwide: single dental degree, single medical degree, dual degrees, combination of medical/dental studies but not degree-based (stomatology), and the hybrid forms. Conclusion OMS remains a dental speciality in the majority of countries in the world, despite earlier claims that dual qualification is superseding single degree training fast, with some countries having also a medical OMS speciality with same scope of practice.